Effect of aging on corrosion behaviour of AA6061 aluminium alloy - Mohd Syahidan, Mohamed Nawi (2012)
The material for experiments was an extruded sheet AA6061 aluminium alloys by thickness of 2 mm. We studied the influence of different artificial aging parameters on corrosion behaviour of Al-Mg-Si alloy. The Al alloys was solution treated at 490±5oC for 5 hours, quenched in oil at room temperature and artificial aging at 170oC, 190oC at different aging time of 60, 180 and 360 minutes respectively. After heat treatment process, the obtained alloys will be etched for microstructure seeking purpose and then were corroded in solution of 3.5% NaCl by conducting potentiodynamic polarization for electrochemical measurement. After corrosion test, samples were prepared for analyzing the surface morphology of corrosion formed after exposed to the chloride media. We observed that the lowest corrosion rate has the sample aged at 170oC for 1 hour. The highest corrosion rate happens at 190oC for 1 hour. At 190oC for 6 hours the maximum hardness is obtained, while corrosion behaviour is better for all samples by comparing with as-received sample.